2018
DOI: 10.1111/jav.01754
|View full text |Cite
|
Sign up to set email alerts
|

High ambient temperatures induce aggregations of chimney swifts Chaetura pelagica inside a roost

Abstract: One proposed advantage of communal roosting in birds is a reduction in the costs of thermoregulation. As thermoregulatory benefits are directly linked to the distance between roosting birds, we examined whether temperature is related to inter‐bird spacing in roosting chimney swifts Chaetura pelagica. To test the hypothesis that huddling is used to reduce the costs of thermoregulation, we predicted that swifts would cluster more at colder temperatures. We mounted an all‐weather camera atop a 61 m tall industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…This was surprising but could be related to local conditions (Illinois compared with New York/New Jersey) or other variables that were not measured. Farquhar et al (2018) found that more swifts would aggregate inside of their roosts at higher temperatures and le Roux et al (2019) showed that Chimney Swifts selected cooler roosts over warmer ones. These studies suggest that thermoregulation plays a role in site selection and roosting behaviour, but that light pollution and season were more important in determining entry times.…”
Section: Additional Environmental Factors Affecting Roost Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…This was surprising but could be related to local conditions (Illinois compared with New York/New Jersey) or other variables that were not measured. Farquhar et al (2018) found that more swifts would aggregate inside of their roosts at higher temperatures and le Roux et al (2019) showed that Chimney Swifts selected cooler roosts over warmer ones. These studies suggest that thermoregulation plays a role in site selection and roosting behaviour, but that light pollution and season were more important in determining entry times.…”
Section: Additional Environmental Factors Affecting Roost Entrymentioning
confidence: 99%
“…However, following widespread deforestation, they adjusted their behaviour and started using artificial structures such as chimneys, which they continue to use almost exclusively (Zammuto & Franks 1981, Zanchetta et al 2014. While the function of communal roosting remains unclear, it has been suggested to serve in minimizing predation and/or for thermoregulation (Zammuto & Franks 1981, Farquhar et al 2018, le Roux et al 2019. The number of birds roosting together in a group changes seasonally, with the largest roosts developing at the onset of autumn migration; however, nonbreeding Chimney Swifts also roost during the breeding season, either in a large group or, in rare cases, sharing a chimney with a breeding pair (Dexter 1974), sometimes with helpers (Dexter 1981).…”
mentioning
confidence: 99%
“…In social spiders (Stegodyphus dumicola) and woodlice (Porcellio scaber), experiments show that individuals enjoy reduced water loss in larger groups (Broly et al, 2014;Vanthournout et al, 2016), suggesting that larger groups will survive better than smaller groups in dry conditions (Bilde et al, 2007). This is even true in small vertebrates such as chimney swifts (Chaetura pelagica), which roost closer together on warmer nights (Farquhar, Morin & Nocera, 2018).…”
Section: (B) Social Grouping and Associationsmentioning
confidence: 99%
“…We focus on four categories of expected abiotic environmental change: (i) increases in temperature (including increases in temperature and dryness, earlier springs in the northern hemisphere and reduced snow cover); (ii) increases in pollution (including light, noise, and chemical pollution); (iii) habitat fragmentation (including changes in habitat complexity and gaps between habitat patches); (iv) more variable weather (including variation in temperature and rainfall) and the increased incidence of extreme events. These categories of change are based on those identified by international reports (Meehl et al, 2000;Bindoff et al, 2013;Field et al, 2014) as well as other reviews on the impacts of changing climates on organisms (Walther et al, 2002;Tuomainen & Candolin, 2010;Hoffmann & Sgrò, 2011;Sih et al, 2011;Poloczanska et al, 2013). We have not considered how changes in overall population density, or changes in interspecific interactions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Roost sites are fundamental for swift ecology, offering protection from predation, providing more stable microclimates, and protection from the elements (Steeves et al, 2014). Roost sites are especially important in poor weather, providing a protected space for groups of swifts to rest, conserve heat (COSEWIC, 2018), and reduce water loss (Farquhar et al, 2018) during suboptimal foraging conditions associated with poor weather. Not only do swifts use these structures throughout the energetically expensive migrations, but also throughout the breeding season (COSEWIC, 2018;Steeves et al, 2014) when they are used by nonbreeders, failed breeders, and the nonincubating member of a successfully breeding pair (COSEWIC, 2018).…”
mentioning
confidence: 99%